Review of "Corporate Designing Religion: Transforming the Visual Identities of Religious Institutions in the Digital Era" by Graham Wiseman - Khasanova, Aizhana (Zeitschrift für junge Religionswissenschaft, 2024)
Reviewed Work: Graham, Wiseman. 2023. Corporate Designing Religion. Transforming the Visual Identities of Religious Institutions in the Digital Era. Vienna: LIT Verlag. 452 pages, 54,90 €, ISBN: 978-3-643-91241-1.